The Italian far right from 1945 to the Russia-Ukraine conflict - Guerra, Nicola 1969- (Routledge studies in fascism and the far right, 2024)
"The Italian Far Right from 1945 to the Russia-Ukraine Conflict provides a comprehensive account of the postwar parliamentary and extra parliamentary far right in Italy. This book explores the ideology, movements and activism of the extreme right and neo-fascists. The recent victory in the Italian parliamentary elections of the 'post-fascist' party Fratelli d'Italia and its leader Giorgia Meloni highlights the importance of such research. The book examines why some of these movements participated with CIA-backing in the 'Strategy of Tension' in the years of the Cold War where terrorist actions aimed to keep Italy in NATO and prevent the Communist Party from coming to power while other extreme-right groups vehemently opposed this and what they considered the dangerous 'Americanization' of the country. It debunks the myth that there was a unified postwar fascist movement in Italy but instead excavates the complex battles within the extreme right as well as with their opponents from the left, and the authorities. This study is necessary to clarify the history and ideological dynamics of a political area still too often shrouded in mystery and whose geopolitical role is still poorly understood and generally underestimated. The analysis is contextualised in the present day by looking at the different perspectives of the Italian far right on the Russian invasion of Ukraine. The book will be of interest to researchers of political history, the Cold War, and Italian history and politics"--